Effect of Graded Hydration on the Dynamics of an Ion Channel Peptide: A Fluorescence Approach - Kelkar, Devaki A. (Biophysical Society, 2005)
Water plays an important role in determining the folding, structure, dynamics, and, in turn, the function of proteins. We have utilized a combination of fluorescence approaches such as the wavelength-selective fluorescence approach to monitor the effect of varying degrees of hydration on the organization and dynamics of the functionally important tryptophan residues of gramicidin in reverse micelles formed by sodium bis(2-ethylhexyl) sulfosuccinate. Our results show that tryptophans in gramicidin, present in the single-stranded β(6.3) conformation, experience slow solvent relaxation giving rise to red-edge excitation shift (REES). In addition, changes in fluorescence polarization with increasing excitation or emission wavelength reinforce that the gramicidin tryptophans are localized in motionally restricted regions of the reverse micelle. Interestingly, the extent of REES is found to be independent of the [water]/[surfactant] molar ratio (w(o)). We attribute this to heterogeneity in gramicidin tryptophan localization. Fluorescence intensity and mean fluorescence lifetime of the gramicidin tryptophans show significant reductions with increasing w(o) indicating sensitivity to increased polarity. Since the dynamics of hydration is related to folding, structure, and eventually function of proteins, we conclude that REES could prove to be a potentially sensitive tool to explore the dynamics of proteins under conditions of changing hydration.